PENGARUH TINGKAT KEAMANAN DAN PELAYANAN PETUGAS AVSEC PASCA EVENT MOTOGP TERHADAP KEPUASAN PENUMPANG DI BANDAR UDARA INTERNASIONAL ZAINUDDIN ABDUL MADJID LOMBOK - Irfan Maulana Haqiqi; Nuning Agustina Ambarsari (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2023)
Lombok's Zainuddin Abdul Madjid International Airport serves as the entry point for visitors and holidaying tourists. The increased movement of aircraft and passengers during MotoGP events will have a direct impact on the airport's ability to provide international standard services, security, comfort and safety for passengers. Aviation Security (AVSEC) plays an important role in ensuring the safety of passengers both on the ground and in the air. This study uses quantitative methods to measure the effect of the level of security and service provided by Avsec officers after the MotoGP event on passenger satisfaction at Zainuddin Abdul Madjid Lombok International Airport. The sig value is 0.000 <0.05. This indicates that the variable level of security and service level have a simultaneous effect on passenger satisfaction. In this study, the R square value obtained was 0.641. Thus passenger satisfaction at Abdul Madjid Lombok International Airport is 64.1% influenced by the variable level of security and level of service.